Enhancement of Permeability Activated by Supercritical Fluid Flow through Granite - Tsuyoshi Nohara; Masaoki Uno; Noriyoshi Tsuchiya (Geofluids)
This geological study utilized electron probe microanalysis of granitic rocks to evaluate traces of hydrothermal fluid activity. Amphibole-plagioclase thermometry was applied to estimate the temperature of a glassy vein as approximately 700°C. The results of mesoscopic and microscopic observations of the rock core obtained through borehole investigations revealed that the track of supercritical fluid flow was microfracture filling with hornblende and plagioclase. Grain-boundary microfractures and parallel microfractures were recognized as traces formed by the limited activity of the supercritical fluid immediately after granite setting in the Late Cretaceous. The current high permeability of a borehole in and around the track of supercritical fluid flow was recognized to be related to the microfracture network. In order to investigate the enhancement of permeability activated by the supercritical fluid flow through granite, the results of this geological study and existing data from in situ permeability tests were analysed. Various fractures in and around the trace of a self-sealing zone were investigated for another borehole rock core. The trace of the self-sealing zone, which was composed of filling textures associated with the supercritical fluid, corresponded to the current low-permeability section of the borehole. Representative types were proposed for simple classification based on the characteristics of fractures and the permeability data of each test section. A high-angle fracture of chlorite filling in combination with an open fracture and the development of a sericite-filling fracture network including a low-angle open fracture were recognized as characteristics of high-permeability types. The results of this study indicate that the enhancement of permeability was activated by supercritical fluid flow through granite.